Venerating saints and constructing cults in an age of reform: male and female monastic communities and their saints in late tenth- and early eleventh-century England - Braund, S (2021)
Why was there a proliferation of saint-making in late tenth- and early eleventh-century England? New saints, ancient saints, universal saints, and obscure saints were venerated with striking vigour. Litanies, calendars, prayerbooks, and Latin and vernacular hagiographical collections attest to a remarkable and devoted interest in the saints of Christian history in this period. The answer to this striking development lies with those responsible for the care of the saints: monasteries and nunneries. While not the unique owners of saints’ relics, both male and female monastic congregations nonetheless presented themselves as uniquely qualified custodians. They achieved this representation by capitalising on an ideology of reform monasticism which began to develop in the second half of the tenth century. Traditionally labelled the ‘Benedictine Reform,’ this period in English history has been studied primarily from the perspective of three episcopal leaders who promoted the reform of monastic life. This thesis foregrounds congregations, rather than the bishops, and reveals that ‘reform’ operated dynamically and outside the control of these reformers. The ideology crafted by the reformers elevated monastic men and women to an exceptional status. Sensitive to the potential of this ideology, new male and female congregations integrated the rhetoric of reform into their cults. They created new cults and revived ancient ones with the rhetoric of reform and monastic exceptionalism. Over the course of the late tenth and early eleventh century, monastic virtue and the language of sanctity became blended as male and female congregations embedded themselves in a scheme of Christian history and an increasingly diverse religious landscape.